Men on the move and the wives left behind: the impact of migration on family planning in Nepal. Issue 1 (1st January 2019) - Shattuck, Dominick; Wasti, Sharada P.; Limbu, Naramaya; Chipanta, Nokafu Sandra; Riley, Christina
Abstract: Nepali migration is longstanding, and increased from 2.3% of the total population in 2001 to 7.2% in 2011. The estimated 1.92 million migrants are predominantly men. Consequently, 32% of married women have husbands working abroad. Social structures are complicated as many married women live with their in-laws who typically assume decision-making power, including access to health services. This study compares access to reproductive health services, fertility awareness, and decision-making power among a sample of married women aged 15–24 years ( n  = 1123) with migrant husbands ( n  = 485), and with resident husbands ( n  = 638). Predictably, women with migrant husbands had significantly lower contraceptive use than other married women (9.3% vs 30.3%, respectively), and expressed a higher intention to become pregnant in the next year. Despite their intentions, women with migrant husbands scored lower on a fertility awareness index, were less likely to discuss pregnancy planning with their spouse, and less likely to describe their relationships positively. Decision-making for both groups of married women was dominated by both husbands and in-laws in different ways. Yet, across multiple normative scales, fewer women with migrant husbands felt pressure to conform to existing social norms. Married women with migrant husbands reflect a subset of women, with unique fertility issues and desires. Interventions that increase knowledge of fertility among this subset of women, promote healthy preconception behaviours. Linking women for counselling opportunities throughout the pre and postnatal periods may help improve health outcomes for mothers and children.